Fault diagnostics of the fuel injection system of a medium power maritime diesel engine with application of acoustic signal - RANACHOWSKI, Z.; BEJGER, A. (Archives of Acoustics, 2005)
The possibilities of application of a portable system for registration of the acoustic signal in the frequency range of 1000-10000 Hz for diagnosing common faults of the fuel injection system of the maritime diesel engine are presented. Clear differences in the registered waveforms are occurring when the records of the working fuel injector are compared with the other ones recorded in the injector with blocked nozzle orifice and when insufficient amount of fuel is delivered. Signal signatures of the operating fuel pump at three operating conditions are also presented. A procedure of comparing the acoustic signals registered on the stub of similar faulty and good engine elements is recommended by the authors as efficient and easy for application.